The Giving Legal Aid For The Poor On A Criminal Case - Ramdhan Kasim (Susbtantive Justice International Journal of Law, 2018)
The purpose of this study is to know and examine and analyze the nature of the provision of legal aid for the poor in criminal cases and to know and review and analyze the role of Legal Aid Organizations in Providing Legal Aid for the Poor in criminal cases. as well as to know and examine and analyze what factors influence the implementation of legal aid of the Poor in criminal cases.